EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI 1 JELIMPO KABUPATEN LANDAK - Suprihatiningsih, Siti (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
AbstractThe low level of mathematics learning achievement is one of the problems that is difficult tosolve. Many factors are related to these problems, one of which is the use of appropriate learningmethods in learning. The purpose of this study is to determine the effectiveness of mathematicslearning using the pairs checks method on mathematics learning achievement. The method used inthis study is a quantitative method with comparative studies, with a prerequisite test of the analysisof the normality test and homogeneity test and hypothesis testing using the t-test. The resultsshowed that the pairing type cooperative learning model was more effective than the directlearning model of learning achievement, it can be seen from the average value of students whowere taught using the pair checks type cooperative learning model that is 73.50 while studentswho were taught with direct learning models has the average value which is 54.18. This isreinforced by the hypothesis testing based on the ratio t_count to t_ (1-Î±) at a significant level of5% or Î± = 0.05 indicating that t_count is greater than t_ (1-Î±) (1.731585> 1.67022).Keywords: methods, pair checks, mathematics.